Sabah football girls rearing to reclaim title - Bingkasan, Lester J. (Borneo Post (KK), 2016)
KOTA KINABALU: Sabah will go all out to regain the Tun Sharifah Rodziah title when the 29th edition of the country's premier women football tournament gets underway at Universiti Utara Malaysia in Sintok Kedah today.